Parasitoid wasps Ophioninae (Hymenoptera: Ichneumonidae) from Arequipa Department, Perú - Suarez, Rodrigo (2021)
The species richness and composition of nocturnal parasitoid wasps Ophioninae subfamily in the Arequipa department was determined. Sixteen localities were evaluated along an altitude gradient that goes from sea level up to 4300 m; in each locality, collections were done in March and May 2018. Light traps were used for the evaluation. A total of 15 morphospecies and 8 species corresponding to the genera: Alophophion, Enicospilus, Eremotylus, and Ophion were registered. The highest richness of Ophioninae was found at 3300 m (S = 8). The genera Alophophion and Ophion were more abundant at medium to high elevations, Enicospilus was more abundant at low altitude localities, and Eremotylus was only recorded in a medium altitude locality.